Strategic public finance - Bailey, Stephen (Palgrave Macmillan, 2004)
Strategic Public Finance is not a conventional treatment of public finance in that it requires no knowledge of economics. It is suitable for multidisciplinary undergraduate and taught postgraduate degree programmes focusing on social policy, social sciences, the welfare state, public administration, politics and public policy. It is especially suitable for Master of Business Administration (MBA) programmes. Its focus being on strategic issues in public finance, the book covers the main alternative political philosophies underpinning public finance, the theoretical impact of collective choices and public finance on property rights, its relative scale in developed countries, spending and raising public finance, potential beneficial and adverse effects of public finance, structural gaps, strategic local public finance, potential use of vouchers to distribute public finance and a strategy for public finance. The comparative analysis of time-series data relating to all OECD countries outlines the present and future challenges for this topical area of finance.